(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This exploratory research looks at how working women acquire and consume quick meals. There has been a sizable change in women’s eating habits as a result of the expanding trend of working women. Understanding the variables that affect working women’s purchases and consumption of quick meals is the goal of this study. The study was carried out utilising a mixed-method approach that included both qualitative and quantitative methodologies among a sample of working women in metropolitan locations. The findings suggest that because quick meals are convenient and time-saving, working women prefer them. A further finding of the study was that consumers’ purchasing and consuming decisions are significantly influenced by flavour, affordability, and nutritional value. The study’s conclusions may be helpful to marketers nd policymakers to develop targeted marketing strategies and policies that cater to the needs of working women and promote healthier food habits.